The Inefficient and Unjust Global Distribution of COVID-19 Vaccines: From a Perspective of Critical Global Justice - Zhehan Li PhD; Jiajun Lu PhD; Jiamin Lv PhD (SAGE Publishing, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has caused huge losses and massive damage to socio-economic development around the globe, which might even potentially evolve into a humanitarian crisis as it continues to spread. In response to the further resulting public threats, collaborative research, rapid production, and efficient and just distribution of vaccines have been given a top priority. However, there exists a serious inefficiency and injustice in the distribution of COVID-19 vaccines among different countries, regions, and social classes currently. Richer countries and regions have acquired far more vaccines than needed, further exacerbating the severity of the epidemic in underdeveloped and marginalized countries and regions. From a perspective of critical global justice, we explore the causes of the inefficient and unjust global distribution of vaccines and comprehensively examine the shortcomings of the current distribution frameworks, such as COVID-19 Vaccines Global Access Facility (COVAX). Then, under the framework of critical global justice, we propose a multi-phase fair priority model that improves the existing proportional distribution mechanism. This solution to the global injustice reoptimizes the cross-border and domestic vaccine distribution and aims to resolve the pandemic more efficiently. The proposed framework and methodology of vaccine distribution could be taken as an opportunity to consistently promote the development of the global socio-economic structure towards global justice more broadly and systematically.